2009
DOI: 10.1007/s00784-009-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study for the 1-year crestal bone maintenance around modified diameter implants with different loading protocols: a radiographic evaluation

Abstract: This study evaluated by standardised digitised periapical radiography the crestal bone maintenance around modified diameter internal hex implants with variable thread design and narrow neck loaded with different procedures. Forty implants were placed in 25 patients. Twenty implants were conventionally loaded, 20 ones immediately loaded. Radiographs were taken with a customised bite record and processed with software. Measurements of bone from the fixture-abutment junction to mesial and distal marginal bone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…Angulated hollow cylinder implants presented a complication rate of 12%. Danza et al (37) reported that crestal bone maintenance around conventionally and immediately loaded modified diameter implants was similar, with slight significant differences in mandible where a lower marginal bone loss was observed.…”
Section: Zaključakmentioning
confidence: 98%
See 1 more Smart Citation
“…Angulated hollow cylinder implants presented a complication rate of 12%. Danza et al (37) reported that crestal bone maintenance around conventionally and immediately loaded modified diameter implants was similar, with slight significant differences in mandible where a lower marginal bone loss was observed.…”
Section: Zaključakmentioning
confidence: 98%
“…Rezultati ovog istraživanja pokazali su veće gubitke marginalne kosti kod implantata postavljenih u prednja područja u odnosu na one u stražnjima, ali nije bilo statistički značajne razlike između maksilarnih i mandibularnih mjesta implantacije godinu dana nakon njihova funkcionalnog opterećenja. Several factors influence implant prognosis and can attribute to implant failure: length and diameter of the implant, implant location, implant designs, bone quality, implant surface and the general health of the patient, functional loading (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(32)(33)(34)(35)(36)(37). In the present study, the patients with systemic diseases have been excluded and implant prognosis was based on the different implant diameters.…”
Section: Zaključakunclassified
“…Understanding the causative factors affecting the RRR would be of great help both in the possible prevention of extensive alveolar ridge resorption and in designing complete dentures that provide a proper functioning of the masticatory apparatus, delaying bone resorption. Some studies revealed that dental implants and overdentures prevent alveolar bone reduction at the implant site and reduce RRR posteriorly of the implant site 5,6 . One study covering a period of 10 years of denture wearing revealed that patients rehabilitated with implant‐retained mandibular overdentures were not subjected to more RRR in the anterior maxilla when compared to patients wearing a conventional CDs, but regarding the mandibular posterior residual ridge, resorption was irrespective of wearing an implant‐retained mandibular overdenture or a conventional mandibular denture 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Danza M et al in his randomized controlled study with 1 year follow-up showed no significant differences for marginal bone loss between immediately and conventionally loaded implants, except for slight significant difference in mandible. 20 In vivo comparative study conducted by Guncu MB et al showed that immediate functional loading did not negatively affect implant stability, marginal bone levels and periimplant health when compared with conventional loading of single tooth implant. 21 Schincagia et al conducted a randomized controlled trial aimed to compare single implant supported mandibular molar restorations using either an immediate or delayed loading protocol.…”
Section: Discussionmentioning
confidence: 99%